Design of a high-resolution liquid xenon detector for positron emission tomography - Backues, Alexander; Feng, Jeremy; Ni, Matthew; Zhong, Min (Frontiers in Detector Science and Technology, 2025)
Positron Emission Tomography (PET) is a vital imaging technique extensively used for early cancer detection by visualizing metabolic processes in the body. While traditional PET systems use scintillation crystals like bismuth germanate (BGO) or lutetium oxyorthosilicate (LSO) to detect gamma rays, they have inherent energy and spatial resolution limitations. This paper proposes an advanced PET design using liquid xenon (LXe)-based detectors that integrate scintillation and ionization energy detection. Our PET detector design has a monolithic liquid xenon target of 5×5×5 cm3, from where scintillation light is detected by silicon photomultipliers (SiPMs) placed on one side of the target. The ionization is converted to field-enhanced electroluminescence in liquid xenon and detected by the same SiPMs. We use Monte Carlo simulations to optimize the configuration of the electric field and improve the light collection efficiency. Combining both detection modes, the proposed system aims to significantly improve the energy resolution to approximately 2% full width at half maximum (FWHM). Furthermore, machine learning models enhance position reconstruction accuracy with sub-millimeter horizontal and depth-of-interaction (DOI) resolutions. The results indicate that the LXe-based PET detector can achieve superior performance compared to current PET technologies, offering enhanced imaging accuracy with the potential for reduced doses of radioactive tracer.